2008
DOI: 10.1007/s10719-008-9127-7
|View full text |Cite
|
Sign up to set email alerts
|

Acceptor substrate specificity of UDP-Gal: GlcNAc-R β1,3-galactosyltransferase (WbbD) from Escherichia coli O7:K1

Abstract: Most of the glycosyltransferases involved in O antigen biosynthesis have not yet been characterized. We recently demonstrated that the wbbD gene of the O7 lipopolysaccharide biosynthesis cluster in E. coli strain VW187 (O7:K1) encodes WbbD, a UDP-Gal: GlcNAcalpha-pyrophosphate-lipid beta1,3-Gal-transferase (EC 2.4.1., accession number AAC27537) that transfers the second sugar moiety in the assembly of the O7 repeating unit. The enzyme utilizes undecaprenol-pyrophosphate-GlcNAc as a natural acceptor substrate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Modifications of the pyrophosphate group eliminated the activity and binding to the enzyme, although the compound having a single phosphate did have 11% activity. None of the GlcNAc analogs tested, which were inactive as substrates, bound to and inhibited WfeD, and we previously reported similar findings for WbbD (8) and for WfgD and WfaP (6). Thus, the pyrophosphate group may be an essential group responsible for the binding of the acceptor to the enzymes that recognize GlcNAc-PP-lipid.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Modifications of the pyrophosphate group eliminated the activity and binding to the enzyme, although the compound having a single phosphate did have 11% activity. None of the GlcNAc analogs tested, which were inactive as substrates, bound to and inhibited WfeD, and we previously reported similar findings for WbbD (8) and for WfgD and WfaP (6). Thus, the pyrophosphate group may be an essential group responsible for the binding of the acceptor to the enzymes that recognize GlcNAc-PP-lipid.…”
Section: Discussionsupporting
confidence: 66%
“…The advantage of GlcNAc␣-PP-(CH 2 ) 11 -OPh is that the substrate and the enzymatic reaction product can be readily detected and separated by HPLC. We have previously shown that this compound was also an excellent substrate for the ␤1,3-Gal-transferase WbbD from E. coli strain VW187 (8,17) and the ␤1,3-Glc-transferases WfgD and WfaP from E. coli serogroups O152 and O56, respectively (6). A similar compound was also shown to be an acceptor for a GalNAc-transferase from E. coli O86:H2 (28).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Based on our experience, we expect that at least one phosphate residue directly linked to GalNAc␣ is an absolute requirement for WbwC, but this remains to be shown upon synthesis of the appropriate acceptor analogs (26,50,51). Previous studies showed that different lipid chains in the acceptor were compatible with high activities of Gal-and Glc-transferases (22,24,48). In the current study, we used two acceptors that differed in the terminal ring structure in the aglycone, suggesting that the structure of the lipid moiety may be of minor importance for in vitro activity.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence has demonstrated that bacterial glycosyltransferases acting on Und-linked acceptors are relaxed in their recognition of lipid moiety (21,27,28). Such flexibility allows for the in vitro construction of an oligosaccharide on an unnatural lipid mimic rather than Und.…”
Section: Assembly Of O-unit-pp-lipid Substrates-most Of E Colimentioning
confidence: 99%